KETAHANAN VARIETAS PADI LOKAL MENTIK WANGI TERHADAP PENYAKIT BLAS - Yulianto Yulianto (Politeknik Negeri Lampung, 2017)
Mentik Wangi, one of the local rice varieties, is highly favored by rice farmers in Central Java. Marketers and consumers highly accept Mentik Wangi with its elliptical seeds because it has delicious taste and aroma. Besides having delicious taste, the variety is resistant to blast disease in various locations, whether planted in lowland or upland. In endemic blast disease areas, Mentik Wangi variety showed resistance to blast disease with low disease intensity, although the other varieties in these places showed quite high disease intensity. Rice blast disease is a disease that damages the rice not only on dry land, but also on rainfed and irrigation lands. At a high level of disease intensity, blast disease can cause yield losses of up to 100%. Planting resistant rice variety to prevent damage due to blast disease is one of the methods to blast disease control which is effective, inexpensive, and safe for the environment. However, control of blast disease with one component such as planting resistant rice is estimated to be ineffective in the long term, because the pathogen causes the blast disease to be able to adapt to the rice variety to form a new race that is more virulent. A rice variety that is originally resistant will gradually become susceptible to the new pathogen race. When the rice varieties which are resistant to blast disease is controlled by a single gene (monogenic resistant), the resistance of these varieties within 2-4 planting seasons will be broken by a new pathogenic race. Mentik Wangi that shows resistance to blast disease in various rice planting regions is expected to have some of the resistance genes, so that it can be used as a durable resistant variety.Â Keywords: Rice, Mentik Wangi, resistance, blast